2015
DOI: 10.1016/j.dnarep.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

RecBCD is required to complete chromosomal replication: Implications for double-strand break frequencies and repair mechanisms

Abstract: Several aspects of the mechanism of homologous double strand break repair remain unclear. Although intensive efforts have focused on how recombination reactions initiate, far less is known about the molecular events that follow. Based upon biochemical studies, current models propose that RecBCD processes double strand ends and loads RecA to initiate recombinational repair. However, recent studies have shown that RecBCD plays a critical role in completing replication events on the chromosome through a mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 124 publications
5
70
0
1
Order By: Relevance
“…The amplification of terminal DNA in a recG mutant has been examined in detail [6, 34, 39, 40], while the DNA loss in the recB mutant has been less extensively explored, and the model of merging forks has not been directly tested experimentally [35, 41]. Here we use Marker Frequency Analysis (MFA) and live-cell fluorescence microscopy to further characterize this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The amplification of terminal DNA in a recG mutant has been examined in detail [6, 34, 39, 40], while the DNA loss in the recB mutant has been less extensively explored, and the model of merging forks has not been directly tested experimentally [35, 41]. Here we use Marker Frequency Analysis (MFA) and live-cell fluorescence microscopy to further characterize this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Failure of even a single completion event would be expected to result in duplications, deletions, rearrangements, or cell death, depending on how the convergent strands are processed. Cells devote a large number of enzymes to maintain the fidelity of both replication initiation and elongation, and recent studies have shown that this final step, required to maintain genomic integrity, similarly requires enzymatic control and is tightly regulated (3,4).…”
mentioning
confidence: 99%
“…In E. coli, the completion of DNA replication requires the RecBCD helicase-nuclease complex and occurs through a reaction that does not involve recombination or RecA (3,4). In the absence of RecBCD, cultures either fail to replicate or fail to maintain the chromosome region where replication forks converge, leading to large segments of the chromosome remaining unreplicated or degraded in this region.…”
mentioning
confidence: 99%
“…RecBCD is one of the most fascinating and studied multienzymatic complexes in bacteria. It is the major recombinational pathway in E. coli responsible for the repair of DSB, conjugational recombination, but also for the degradation of foreign linear DNA, and recently RecBCD was shown to participate in completion of DNA replication (41,42). We unravel here that, in addition to these many functions, RecBCD also plays a role in SSG repair.…”
Section: Discussionmentioning
confidence: 80%